Dispersal altering local states has a limited effect on persistence of a metapopulation. Issue 1 (1st January 2018) - Xu, Jingjing; Wild, Geoff
ABSTRACT: Metapopulations are collections of local populations connected by dispersal. Metapopulation models often assume would-be colonists affect the states of local populations they disperse from and those they disperse to. Here, we build a new framework to include that effect and to assess the impact of dispersal. Our model predicts that a metapopulation will, in general, be found either in the state of global extinction or in the state of persistence. Our key finding is that dispersal, and the state changes associated with dispersal, have significant qualitative and quantitative effects on long-term dynamics only in a narrow range of parameter space. We conclude that life history features other than dispersal (e.g. mortality rate) have a greater influence over metapopulation persistence. We discuss the implications of our results for conservation biology, the future application of our model to the study of cooperative breeding, as well as our model's limitations.